Rangkap Jabatan Anggota Kepolisian Republik Indonesia (Tinjauan Yuridis Kepatuhan dan Profesionalitas Kepolisian Pasca Putusan Mahkamah Konstitusi Nomor 114/PUU-XXIII/2025) [Holding Multiple Positions by Members of the Indonesian National Police (A Juridical Review of Police Compliance and Professionalism Post Constitutional Court Decision Number 114/PUU-XXIII/2025)] - Suheflihusnaini Ashady; Aryadi Almau Dudy (Indonesia Berdaya, 2026)
The Directorate of Vital Object Security of the South Sulawesi Regional Police (Ditpamobvit Polda Sulsel) plays an important role in securing Very Important Person (VIP) guests in the South Sulawesi region. This role includes conducting inspections of visitors or participants attending VIP guest events and serving as a personal escort team (walpri) for VIP guests. This study aims to understand the role of the Directorate of Vital Object Security of the South Sulawesi Regional Police in securing VIP guests and to identify obstacles faced by Ditpamobvit Polda Sulsel personnel in carrying out VIP guest security in South Sulawesi. The study found several challenges in securing VIP guests, including the large number of security locations occurring simultaneously which results in insufficient security equipment such as Secdoor, a shortage of personnel in the Directorate, sudden changes in VIP guest schedules, VIP guests’ desire to interact more closely with the public, and the open nature of security locations. Abstrak. Direktorat Pengamanan Objek Vital Kepolisian Daerah Sulawesi Selatan (Ditpamobvit Polda Sulsel)  memiliki peran penting dalam pengamanan tamu Very Important person (VIP) di wilayah Sulawesi Selatan Peran tersebut yaitu melaksanakan pemeriksaan kepada pengunjung atau peserta kegiatan tamu VIP dan menjadi tim pengawal pribadi (walpri) pada tamu VIP Penelitian ini bertujuan untuk mengetahui peran Direktorat Pengamanan Objek Vital Kepolisian Daerah Sulawesi Selatan dalam pengamanan tamu VIP dengan adanya penelitian ini dapat mengetahui hambatan yang dihadapi oleh personil Ditpamobvit Polda Sulsel dalam melaksanakan pengamanan tamu VIP di wilayah Sulawesi Selatan. Ditpamobvit Polda Sulsel masih menemukan kendala dalam melaksanakan pengamanan tamu VIP yaitu dalam hal banyaknya lokasi pengamanan dalam waktu yang bersamaan membuat alat yang digunakan dalam pengamanan tamu VIP seperti Secdoor masih  kurang, masih kurangnya personil pada Direktorat Pengamanan Objek Vital Kepolisian Daerah Sulawesi Selatan, perubahan jadwal kegiatan oleh tamu VIP yang secara mendadak, keinginan tamu VIP yang ingin berinteraksi lebih dekat dengan masyarakat, serta lokasi pengamanan yang terbuka.